Rosja – „pierwsza miłość i więzienie”. Konfrontacja z przeszłością w „Dziennikach” Igora Gubermana - Lenart, Agnieszka (Studia Rossica Posnaniensia, 2019)
The article focuses on the relationship with the past, which is seen from the point of view of the emigrant, both Russian and Jewish, and his complex identity. The analysis is done on the basis of Igor Guberman’s Diaries, in which an ambivalent attitude to the homeland is observed.